Esketamine Treatment for Depression in Adults: A PRISMA Systematic Review and Meta-Analysis. - Fountoulakis, Konstantinos N.; Saitis, Athanasios; Schatzberg, Alan F. (American Journal of Psychiatry, 2025)
Objective: Intranasal esketamine has been approved as an adjunctive therapy for treatment-resistant major depressive disorder with acute suicidal ideation and behavior. The authors conducted a systematic review and meta-analysis of the available data on its efficacy against depression and suicidality as well as its side effects. Methods: MEDLINE was searched with the keyword "esketamine" on March 24, 2024, using the PRISMA method. Data processing and statistical analysis were performed with R, version 4.3.3, and the meta-analysis was performed with the METAFOR package. Results: Of 1,115 articles initially identified, 87 were included for analysis and discussion. At weeks 2–4, randomized controlled trials were mostly negative or failed; however, the meta-analysis returned a weak but significant positive effect for depression (effect size range, 0.15–0.23 at weeks 2–4), similar to augmentation strategies with atypical antipsychotics for treatment-resistant depression. The effect size concerning suicidality was not significant at any time point. The sensitivity analysis produced the same results. Conclusions: The study findings suggest that esketamine's efficacy as an add-on to antidepressants is modest in treatment-resistant depression (similar to augmentation strategies with atypical antipsychotics) and is absent against suicidality itself. These findings need to be considered in light of esketamine's abuse potential and the fact that long-term effects are still not fully known. Some alarming signs concerning deaths and emerging suicidality during the testing phase are discussed, along with other regulatory issues.